Research on performance of jet refrigeration cycle driven by waste heat of refrigerated vehicle - Jiang, Shujun; Pan, Xiubin; Zhang, Song; Huang, Yanmei; Que, Wenshuai; Sang, Hailang; Guan, Wei (Frontiers in Energy Research, 2024)
Nowadays, refrigerated food preservation and refrigerated transport vehicles are very widespread. But in a vehicle’s engine, a significant portion of the heat is emitted to the environment in the form of exhaust gas and jacketed water. If the cooling system is used to convert this part of the waste heat into cold energy, the thermal efficiency of the fuel will be improved to a certain extent. Therefore, this paper uses two jet refrigeration systems to recover heat from refrigerated truck exhaust and jacket water. This paper considers two waste heat recovery injection refrigeration systems, one is a conventional injection refrigeration system, which only uses the engine exhaust as a heat source; the other system is based on the conventional system, which adds a preheater before the generator and uses engine jacket water to preheat the working fluid. This paper compares the system performance under different working fluids, and considers the effects of operating temperature and secondary flow pressure drop in the ejector receiving chamber on the system performance. The results of the study showed that with the addition of the preheater, the cooling capacity of the system was much higher than that of the conventional system. When the working fluids R141b/R245fa and R142b/R134a are selected, the system performance is better, where the optimal mass fraction ratios are R141b/R245fa (0.3/0.7 and 0.4/0.6), R142b/R134a (0.6/0.4).